Insulin secretion from beta cells within intact islets: Location matters. (April 2015) - Hoang Do, Oanh; Thorn, Peter
Summary: The control of hormone secretion is central to body homeostasis, and its dysfunction is important in many diseases. The key cellular steps that lead to hormone secretion have been identified, and the stimulus‐secretion pathway is understood in outline for many endocrine cells. In the case of insulin secretion from pancreatic beta cells, this pathway involves the uptake of glucose, cell depolarization, calcium entry, and the triggering of the fusion of insulin‐containing granules with the cell membrane. The wealth of information on the control of insulin secretion has largely been obtained from isolated single‐cell studies. However, physiologically, beta cells exist within the islets of Langerhans, with structural and functional specializations that are not preserved in single‐cell cultures. This review focuses on recent work that is revealing distinct aspects of insulin secretion from beta cells within the islet.